The Impact of Nashirudin Al Albani's Tarjih Hadith Method on Differences in Mazhab and Qur'anic Interpretation - Saladin, Bustami; Taufiq, Muhammad; Ibni Syatirah, Sebti (Diroyah : Jurnal Studi Ilmu Hadis, 2023)
The Impact of Nashirudin Al-Albani's Tarjih Hadith Method on Differences in Mazhab and Qur'anic Interpretation" explores the significant influence of Muhammad Nasiruddin al-Albani, a 20th-century Islamic scholar, on Islamic jurisprudence and Quranic exegesis. Al-Albani is noted for his rigorous and critical approach to the evaluation of á¸¤adith (Tarjih), which often diverged from traditional scholarly consensus, leading to varying interpretations within different Islamic schools of thought (Mazhabs). The study highlights Al-Albani's method of assessing Hadiths through an in-depth analysis of their Sanad (chain of narrators) and text (matan), often leading to the reassessment of their validity. This paper discusses the strengths and weaknesses of his method, noting how his stringent criteria for Hadith evaluation have impacted Islamic legal judgments and interpretations of the Quran. The article also delves into the societal and cultural implications of Mazhabs in religious life, emphasizing how Al-Albani's interpretations have influenced religious practices and law. It underscores the importance of a balanced approach to understanding and applying Hadith in Islamic law, considering historical, social, and contextual factors. Employing a qualitative research methodology with a library research approach, the study analyzes various literature sources to provide a comprehensive overview of Al-Albani's impact on Islamic jurisprudence. It concludes by emphasizing the need for a more comprehensive and contextual understanding of Hadith and Quranic interpretation to avoid superficial understandings and embrace a richer, more accurate understanding of Islamic teachingsÂ